Desenvolvimento de consórcio bacteriano de Bacillus subtilis e Pseudomonas aeruginosa imobilizado em poliuretano para biorremediação do corante Vermelho Congo - Trevizan, Caio Eduardo (Universidade Federal de São Carlos, 2025)
Azo dyes rank among the most persistent pollutants in industrial effluents, particularly those from the textile sector. Owing to their high solubility, chemical stability and toxic potential, improper disposal poses a significant environmental risk. Microbial consortia that couple biosorption with biodegradation have emerged as sustainable alternatives to conventional physico-chemical treatments. This study aimed to evaluate the removal of the azo dye Congo Red by pure and mixed cultures of Bacillus subtilis and Pseudomonas aeruginosa and to test whether immobilising the consortium in a synthetic matrix could enhance the system’s stability and reusability. The strains were reactivated and grown in TSB broth, and their compatibility was confirmed in co-cultures. Dye decolourisation assays were then carried out at 100, 200 and 300 mg/L for 48 h, distinguishing biosorption from biodegradation through heat-inactivated cells, desorption tests and FTIR analysis. Biofilm formation was quantified in microplates, and the consortium was immobilised on sterilised polyurethane foam and subjected to three batch cycles using simulated textile effluent. The consortium removed 95±3% of the dye at 100 mg/L and 82±4% at 200 mg/L, outperforming the individual cultures. Efficiency dropped to 54±6% at 300 mg/L, indicating inhibition at higher concentrations. Desorption remained below 12%, and FTIR revealed a 68±5% reduction in the azo band at 1580 cm⁻¹, confirming biodegradation as the main mechanism. B. subtilis exhibited the higher biofilm index, whereas P. aeruginosa initiated azo-bond cleavage. Immobilisation allowed dye removal above 70%. These results demonstrate that an immobilised bacterial consortium is a promising strategy for the biological pre-treatment of textile effluents containing Congo Red.
Development of a bacterial consortium of Bacillus subtilis and Pseudomonas aeruginosa immobilized in polyurethane for bioremediation of Congo Red dye
Keywords: Biossorção; Biodegradação; Biofilme bacteriano; Efluentes têxteis; FTIR; Biosorption; Biodegradation; Bacterial biofilm; Textile effluents; FTIR spectroscopy; CIENCIAS BIOLOGICAS::MICROBIOLOGIA